2020
DOI: 10.5713/ajas.19.0663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of line and floor type on growth performance and feather characterization during the growth period of White Roman geese

Abstract: Objective: The purpose of this study was to investigate whether goose growth and feather characteristics are influenced by their line and feeding surroundings, inclusive of floor materials and types, since there are no reports regarding these factors.Methods: The 240 White Roman geese which were hatched and sex identified came from 3 commercial goose farms. They were randomly distributed to 24 pens depending on a completely random design. The study continued for 13 weeks and included 3 lines of commercial gees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
5
2
Order By: Relevance
“…The discrepancy in the findings might be related to differences in animal species, water pool designs, water pen space ratios, litter materials, floor designs, and stocking density [ 16 , 17 , 31 , 50 ]. The stocking density in this study was lower than that in other studies using perforated floors (0.74 goose/m 2 vs. 1.01 to 7.5 goose/m 2 ) [ 31 , 33 , 61 , 62 ].…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The discrepancy in the findings might be related to differences in animal species, water pool designs, water pen space ratios, litter materials, floor designs, and stocking density [ 16 , 17 , 31 , 50 ]. The stocking density in this study was lower than that in other studies using perforated floors (0.74 goose/m 2 vs. 1.01 to 7.5 goose/m 2 ) [ 31 , 33 , 61 , 62 ].…”
Section: Discussioncontrasting
confidence: 86%
“…Although we did not observe any effect of the floor type on the feather quality score of geese, the proportion of geese whose feather quality was damaged by injurious pecking decreased when geese were raised on perforated plastic floors at the age of 84 days. Lin et al [ 33 ] reported that geese raised on a cement strip floor had longer main wing feathers at the age of 84 days than those raised on a cement floor. Chen et al [ 36 ] observed that ducks raised in plastic nets had better feather quality scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, domestic geese are generally reared in large groups on the floor and allowed to mate naturally ( Lin et al., 2020a ). The breeding efficiency of males has always been a concern for goose breeders ( Jerysz and Lukaszewicz, 2013 ), and there are seldom reports concerning the relationship between SR and PE in geese because of the inability to distinguish and observe individual ganders’ MA and trace the genetic relationship between parent and offspring in large breeding populations ( McDonald et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among Anseriformes, most are similar to the Muscovy duck. Male geese have a significantly higher body weight, back length, sternum length, and chest circumference than females at 13 to 25 wk of age ( Lin et al, 2023 ). At 113 wk of age, Dworka ducks of breeding strain D11 yielded significantly heavier carcasses compared to Pekin ducks of conservative strain P9 ( Kokoszynski et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%